The Processing of Unfair Labor Practice Cases in the United States and Ontario - Bruce, Peter (Relations industrielles / Industrial Relations, 1990)
Although many U.S./Canadian differences in union recognition law have been adequately analyzed, some have been overlooked — particularly differences in the frequency with which labor boards on both sides of the border dismiss unfair labor practice (ULP) cases, and the speed and fairness with which they expedite their ULP litigation. This paper analyzes these differences in detail, referring for Canada to the Ontario Labour Relations Board. It shows why they are important, how they stem from national differences in governmental structure, how they interact with other aspects of union recognition policy, and how they affect outcomes in certification cases and ultimately union growth.